If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4f + -2g + -1f + 6f = 0 Reorder the terms: 4f + -1f + 6f + -2g = 0 Combine like terms: 4f + -1f = 3f 3f + 6f + -2g = 0 Combine like terms: 3f + 6f = 9f 9f + -2g = 0 Solving 9f + -2g = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '2g' to each side of the equation. 9f + -2g + 2g = 0 + 2g Combine like terms: -2g + 2g = 0 9f + 0 = 0 + 2g 9f = 0 + 2g Remove the zero: 9f = 2g Divide each side by '9'. f = 0.2222222222g Simplifying f = 0.2222222222g
| x(10+2x)=3600 | | 7x-20=3x+17 | | -16=-42 | | 0.25k-2=3 | | 7x-6=28 | | x^2+82x+525=0 | | .9(5x+15)=2.2-(x+3) | | 40+0.05=0.15 | | 3(3x-7)=6 | | 38/19=n/20 | | 4x-5*0=12 | | t=2-2[2t-3(1-t)] | | 4B+5A=3 | | 3+1.25*-2.4= | | -3d+4-9d+12=0 | | 5x+5(-5)=75 | | 2x-16=32-x | | 2secx+2x-3=0 | | 4(2m-n)-3(2m-n)=16 | | R+8-3r=-3r+5r+4 | | 5(x-4)+2=3(x-6)-8x | | 4(2m-n)-3(2m-n)=-3 | | 2(x+3)=27 | | 6x^2-48x+32=0 | | 30+3x=174 | | 3(p+5)=18 | | 16-4y=-32 | | 1-y=-3y+9 | | 4(x-3)=2(x-6)-6x | | 8x-11=9x+2 | | R+8-3r=-3+5r+4 | | 12z+4z-10z-5z=15 |